Specificity of Biogenic Selenium Nanoparticles for Prostate Cancer Therapy With Reduced Risk of Toxicity: An in vitro and in vivo Study - Sonkusre, Praveen (Frontiers in Oncology, 2020)
Selenium deficiency is associated with many physiological disorders including the high risk of cancer. The rehabilitation of selenium with different selenium supplements, however, fails due to their low therapeutic index. Therefore, it is advantageous to have a less toxic form of selenium for supplementation with potentially high anticancer activity. Here we show Bacillus licheniformis derived biogenic selenium nanoparticles at a minimal concentration of 2 μg Se/ml induce necroptosis in LNCaP-FGC cells, without affecting the RBC integrity. Real-time gene expression analysis indicated the overexpression of tumor necrotic factor (TNF) and interferon regulatory factor (IRF1) and decreased expression of androgen receptor (AR) and prostate-specific antigen (PSA). Furthermore, histopathological analysis showed the subsequent oral administrations of 10 times higher concentration of these endotoxin free selenium nanoparticles in C3H/HeJ mice (50 mg Se/kg of body weight), induce significantly lower toxicity compared to the L-selenomethionine (5 mg Se/kg). Our study suggested that the biogenic SeNP could emerge as the safest form of selenium supplementation with potent anticancer activity.